Guizhi Fuling Wan ameliorates concanavalin A-induced autoimmune hepatitis in mice - Shun-Li Kuo; Chun-Han Su; Kuei-Hung Lai; Yu-Chia Chang; Jyh-Sheng You; Hsin-Hsin Peng; Chun-Hong Chen; Chi-Chen Lin; Po-Jen Chen; Tsong-Long Hwang (Biomedical Journal)
Background: Autoimmune hepatitis (AIH) is an immune-mediated hepatic disease associated with intense complications. AIH is more common in females and needs effective drugs to treat. Guizhi Fuling Wan (GZFLW) is a traditional Chinese herbal formula for treating various gynecologic diseases. In this study, we aim to extend the new use of GZFLW for AIH. Methods: The tandem MS-based analysis was used to identify secondary metabolites in GZFLW. Therapeutic effects of GZFLW were tested in a concanavalin A (Con A)-induced AIH model in mice. Ethnopharmacological mechanisms underlying the antiapoptotic, antioxidant, and immunomodulatory protective effects were determined. Results: Oral administration of GZFLW attenuates AIH in a Con A-induced hepatotoxic model in vivo. The tandem MS-based analysis identified 15 secondary metabolites in GZFLW. The Con A-induced AIH syndromes, including hepatic apoptosis, inflammation, reactive oxygen species accumulation, function failure, and mortality, were significantly alleviated by GZFLW in mice. Mechanistically, GZFLW restrained the caspase-dependent apoptosis, restored the antioxidant system, and decreased pro-inflammatory cytokine production in the livers of Con A-treated mice. Besides, GZFLW repressed the Con A-induced hepatic infiltration of inflammatory cells, splenic T cell activation, and splenomegaly in mice. Conclusions: Our findings demonstrate the applicable potential of GZFLW in treating AIH. It prompts further investigation of GZFLW as a treatment option for AIH and possibly other hepatic diseases.